Chemical Characteristics of Collagen Extract from Scapula of Bali Cattle (Os scapula) Produced Using Different Extractant - Said, Muhammad Irfan; Abustam, Effendi; Wahab, Abd Wahid; Sartini,; Hifizah, Amriana (Pakistan Journal of Nutrition, 2015)
Collagen is a hydrocolloid products of animal protein resulted in partial hydrolysis. Cow bones abattoir by-product is a product that is rich in collagen proteins, thereby it’s potentially as a source of raw materials. The protein collagen is now widely used as a dietary supplement. This study aimed to evaluate the chemical properties of the extract collagen product from os scapula of Bali cattle through the application of some types of extractant in the production process. Laboratory experimental method was used in this study. A total of four types of extractant was applied, namely: (1) distilled water, (2) ethanol 60% (v/v), (3) CH3COOH 0.5 M and (4) Ca(OH)2 0.5 M. The pattern of Complete Randomized Design (RAL) of Undirectional pattern and the analysis of variance was used as the study design and data analysis, while Duncan's Multiple Range Test (DMRT) was used as a further test if it was significant. The results showed that the use of different extractant extracts on the collagen production processes using raw materials from os scapula of Bali cattle affected (p0.05) on lipid levels and phosphorus levels. Extract collagen from os scapula of Bali cattle produced using four types of extractants have functional properties identical functional groups based on the presence of CO, C-O, OH, CH and N-H bond.